The Theory of Human Capital Revisited: On the Interaction of General and Specific Investments - Anke S. Kessler; Christoph Lülfesmann (Center for Economic Studies and ifo Institute (CESifo), 2002)
Human capital theory distinguishes between training in general-usage and firm-specific skills. In his seminal work, Becker (1964) argues that employers will not be willing to invest in general training when labor markets are competitive. However, they are willing to invest in specific training because it cannot be transferred to outside firms. The paper reconsiders Becker's theory. We show that there exists an incentive complementarity between employersponsored general and specific investments: the possibility to provide specific training leads the employer to invest in general human capital. Conversely, the latter reduces the hold-up problem that arises with respect to the provision of firm-specific training. We also consider the virtues of long-term contracting and discuss some empirical observations that could be explained by the model.
Keywords: C78; D82; L14; L15; 330; human capital formation; general and specific training; hold-up problem.